Marxist view on global political economy and new market trends - Zhang, Fengrong (2023)
Capitalism was always dishonest. However, capitalism has generated massive wealth. Capitalism has been linked to exploitation, wealth inequality, economic collapse, and world strife. Political economy has studied capitalism’s multiple faces. Can capitalism’s problems be eliminated while retaining its benefits, as proponents claim? Capitalism can only be eliminated by limiting or abolishing it, say some critics. This issue’s outcome is largely influenced by theory. Economists believe markets are fair for assessing and rewarding economic contributions to society. Individual inadequacy, not market dominance, causes social and individual problems. The Marxian notion that production relations underpin every society is the key to understanding the contemporary breakdown of order. Class structures sustain political, cultural, and ideological institutions. New production relations, or “no class” interactions, are needed to create a postcapitalist society. Just as new economic relationships arose over the centuries during Europe’s transition from feudalism to industrial capitalism, and a new society developed on the foundation of these systems, so new manifestations of monumental growth in production will evolve in the coming generations to reduce crisis-stricken times. Banks needed a rescue after the global economy collapsed in late 2007. Market economies are not self-regulating. Since it upended traditional patterns of thinking, the disaster allowed people to reconsider long-standing issues that had never been resolved. After the crisis, Marx’s “Capital” sold well worldwide, according to booksellers. Marxism is making a return. Due to its critical legacy in the humanities and social sciences, Marxism cannot be confined in a 19th-century framework. Marx permeated our water and air even while he was rejected. Marxism is everywhere in the 21st century. Modern Marxism supports entrepreneurship and free enterprise if they improve society.